HUBUNGAN PERSEPSI PENDERITA TB PARU TENTANG PENCEGAHAN PENULARAN DENGAN UPAYA PENCEGAHAN PENULARAN TB PARU - Dwi, Binarti; Khaqul Mubin, Ningsih (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Pulmonary TB patient softendo not have the habit of closing the mouthwhen coughing, it certainly can makethe transmission of pulmonary TB in healthy personsin the vicinity. This study aimstoanalyze the relationship of pulmonary TB patient perceptions about prevention of transmission of pulmonary tuberculosis with pulmonary TB prevention efforts. The design used in this study is an analytic correlation with cross sectional. This study uses total sampling so that the sampleis 22 respondents. Independent variablein this study is the perception of pulmonary tuberculosis patients on prevention of transmission and the dependent variableis the prevention of pulmonary TB transmission. Datawere collected using aquestion naireand analyzed using cross tabulation. The results showed the majority of respondents had a negative perception take steps to preventtrans mission of pulmonary tuberculosis with unfavorableby 10 respondents (83.3%). Results of cross-tabulations how ed there is a relationship between the perception of pulmonary tuberculosis patients on prevention of transmission to the prevention of pulmonary TB transmission. The more positive perception of the better prevention was done, and vice versa. In order for pulmonary tuberculosis prevention efforts well underway, much needed positive perception about the prevention of pulmonary TB transmission.Password: perception, Pulmonary TB